2021
DOI: 10.1159/000520643
|View full text |Cite
|
Sign up to set email alerts
|

Foley Catheter Tourniquet for Uncontrollable Extra-Uterine Placental Hemorrhage: Description of a Novel Surgical Technique

Abstract: Introduction Hemorrhage from a partially or fully detached placenta with an advanced abdominal pregnancy can be profuse and catastrophic. The general approach to placenta management is removal of “all or nothing’’. In the event of acute hemorrhage, every attempt to achieve hemostasis quickly is critical. The Foley catheter has shown utility when used to control placental hemorrhage or as a temporary tourniquet applied around structures surrounding the implantation site to aid placental removal with minimal hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In our institution, the double tourniquet technique has been used since 2015 and all surgeries have been performed by a multidisciplinary team, as indicated. In most of the reviews, different methods of blood loss control to lower flow momentarily were proposed and some have explored the utility of the tourniquet in gynecological as well as obstetrical surgeries 11,12 . In a retrospective study, Jingrui Huang et al 13 reported surgical outcomes of using single tourniquets and forceps for vascular control in patients with placenta accreta, with good results, with differences depending on whether the tourniquet was applied above or below the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, the double tourniquet technique has been used since 2015 and all surgeries have been performed by a multidisciplinary team, as indicated. In most of the reviews, different methods of blood loss control to lower flow momentarily were proposed and some have explored the utility of the tourniquet in gynecological as well as obstetrical surgeries 11,12 . In a retrospective study, Jingrui Huang et al 13 reported surgical outcomes of using single tourniquets and forceps for vascular control in patients with placenta accreta, with good results, with differences depending on whether the tourniquet was applied above or below the placenta.…”
Section: Discussionmentioning
confidence: 99%